2021
DOI: 10.18502/ijaai.v20i2.6051
|View full text |Cite
|
Sign up to set email alerts
|

Association of rs3135500 and rs3135499 Polymorphisms in the MicroRNAbinding Site of Nucleotide-binding Oligomerization Domain 2 (NOD2) Gene with Susceptibility to Rheumatoid Arthritis

Abstract: The nucleotide-binding oligomerization domain 2 (NOD2) is the key regulator of inflammatory responses and has been involved in the pathogenesis of rheumatoid arthritis (RA). Laboratory and in silico evaluations have demonstrated that some polymorphisms in 3ˊUTR of NOD2 gene could influence the secondary structure of this region and similarly thermodynamic features of hybridization site and finally deregulate the expression of NOD2. In the current study, for the first time, we evaluated the possible association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Our results showed that rs934734 in SPRED2 is a strong determinant for the development of RA and clinicopathological characteristics of this disease. In our previous studies, similar results were also found about association of specific polymorphisms with clinico-pathological characteristics of RA disease including variants in NLRP3 , NOD2 , and microRNA-124 genes 30 32 .…”
Section: Discussionsupporting
confidence: 83%
“…Our results showed that rs934734 in SPRED2 is a strong determinant for the development of RA and clinicopathological characteristics of this disease. In our previous studies, similar results were also found about association of specific polymorphisms with clinico-pathological characteristics of RA disease including variants in NLRP3 , NOD2 , and microRNA-124 genes 30 32 .…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, the AA genotype shows higher disease activity and MTX toxicity than the AG/GG genotypes ( 29 ). The AA and AG genotypes in the miRNA binding site rs3135500 of NOD2 are significantly associated with the risk of RA, with rs3135500 (A allele) showing a significant relationship with increased erythrocyte sedimentation rates (ESR) and C-reactive protein (CRP) concentrations ( 30 ). However, some studies showed inconsistent results in Polish ( 24 ), Mexican ( 25 ), and Chinese ( 19 , 20 , 31 , 32 ) populations, suggesting that genetic polymorphisms of miR-146a and miR-499 are not significantly associated with RA susceptibility.…”
Section: Genetic Variations In Mirnas Explains Susceptibility Of Ramentioning
confidence: 99%